All my life [videorecording (DVD)] - Rothe, Jessica; Shum, Harry, Jr., 1982-; Allen, Kyle, 1994-; Fit, Chrissie (Universal Pictures Home Entertainment, 2021)
Based on a powerful true story, it follows the journey of a young engaged couple who make the difficult decision to accelerate their wedding in the wake of a devastating discovery. In a race against time, they launch a crowdfunding campaign that spreads the story of their inspiring love far and wide to help create their dream wedding. This year, love like there's no tomorrow.